Seasons, herd mobility and management drive feed intake and digestibility in grazing cattle in West African landscapes - Assouma, Mohamed Habibou; Lecomte, Philippe; Hiernaux, Pierre; Ickowicz, Alexandre; Decruyenaere, Virginie; Blanchard, Mélanie; Wade, Coly; Bois, Bérénice; Corniaux, Christian; Guichard, Françoise; Vayssières, Jonathan (Frontiers in Animal Science, 2025)
Estimating the daily diet of grazing cattle from available feed resources in pastoral and mixed crop-livestock systems in tropical West Africa remains a challenge. The objective of this study was to describe the relevance of cattle diet monitoring across the seasons to better assess the livestock-resources interactions in its local environment in the region. We analyzed seasonal profiles of the diet of grazing cattle in five sites distributed along the Sudano-Sahelian climate gradient from an arid to a sub-humid bioclimate. In the five sites (ranked from the driest to the wettest: Widou, Dahra, Niakhar, Koumbia, Kolda), the feeding behavior of grazing cattle was monitored and feces were collected monthly for one year to estimate dietary intake and digestibility. All the conserved dry samples (n = 1,186) underwent near infrared spectroscopy (NIRS) analyses. The resulting spectral data were compared with a large set of spectral reference data (n=4,138) to predict dry matter intake (DMvi_Fnir DM; g.kgMW-1) and digestibility (dMO_Fnir,%OM) using an updated NIRS “local calibration” procedure. Daily fodder intake ranged from 38.90 ± 6.35 in the hot dry season to 83.86 ± 8.73 gDM.kgMW-1.d-1 in the late wet season. Estimated diet organic matter digestibility ranged from 53.6 ± 8.51% in the hot dry season to 74.3 ± 3.52% in the early wet season. Estimated by aggregation, the total annual intake of a tropical livestock unit (TLU, i.e. a standard 250 kg live weight animal) ranged from 1,236 ± 255 kgDM.TLU-1.year-1 in Dahra to 1,560 ± 142 kgDM.TLU-1.year-1 in Widou. This was well below the 2,281 Kg.DM annual estimate derived from a standard intake of 2.5% LW in DM. Taking digestibility into account, the summed annual metabolizable energy (ME) intake values ranged from 9,858 ± 2,077 Mj.TLU-1.year-1 in Dahra to 13,929 ± 2,345 Mj.TLU-1.year-1 in Koumbia. While important gaps appear during the dry season in some locations, this covered the annual basal maintenance requirements of a TLU, which, based on international standards, are estimated at 7,819 Mj.TLU-1.year-1 (21.4 Mj.day-1). This leaves ME at varying extend, to cover the needs for growth, milk production and reproduction. Tested in a GLM, the variations in in the dependent variables (the daily DM intake, diet digestibility, and ME intake) were analyzed in relation to the independent factors location (study site) and season, as well as their interaction. Results showed that, seasonal effects largely explained the observed variability across the five sites, while differences in herd management practices modulated these effects.